Microbial Volatiles: Small Molecules with an Important Role in Intra- and Inter-Kingdom Interactions - Schulz-Bohm, Kristin; Martín-Sánchez, Lara; Garbeva, Paolina (Frontiers in Microbiology, 2017)
DDuring the last decades research on the function of volatile organic compounds focused primarily on the interactions between plants and insects. However, microorganisms can also release a plethora of volatiles and it appears that microbial volatile organic compounds (mVOCs) can play an important role in intra- and inter-kingdom interactions. So far, most studies are focused on aboveground volatile-mediated interactions and much less information is available about the function of volatiles belowground. This minireview summarizes the current knowledge on the biological functions of mVOCs with the focus on mVOCs-mediated interactions belowground. We pinpointed mVOCs involved in microbe-microbe and microbe-plant interactions, and highlighted the ecological importance of microbial terpenes as a largely underexplored group of mVOCs. We indicated challenges in studying belowground mVOCs-mediated interactions and opportunities for further studies and practical applications.